A Review of the Role of Microbial Forensics amidst Bioterrorism Threats and Strategic st Measures needed to be taken in the 21 Century World and India - Barman , D D (Journal of Indian Academy of Forensic Medicine, 2023)
Bioterrorism is defined as the deliberate release or threaten to release deadly microbial organisms to cause damage to human lives, damage  to live stocks and crops. Various countries and governments around the world have invested in setting up biolaboratories to conduct  research on various pathogens. Microbial Forensics is the field of Forensic Science which apply the scientific principles of Microbiology  and deal with the investigation and identification of suspected bioterror attacks, bio crime, and suspected accidental release of microbial  agents or their toxins from a laboratory facility. The biological agents are commonly transmitted through oral, inhalational, and cutaneous  routes. During the preparation of this review, scientific papers related to the topic of bioterrorism and Forensic Microbiology were  searched using Scopus, PubMed, Google scholar and ProQuest. The search was focused on using key word, such as microbial agents,  biological agents, bioterrorism, and microbial forensics. There is need for development of greater capacity in handling cases of natural as  well as man developed biological agent attack. In this regard nations must work together by applying standard and structured Forensic  Microbiology investigative procedures with use of state-of-the-art technology and tests. India too must build an effective mechanism and  strategy to tackle any future event of biological agent led terror and this would need coordinated policy and approach of the major  stakeholders.
Keywords: Bioterrorism; Microbial forensics; Biological agents; Global; India